Effects of helium adsorption in carbon nanopores on apparent void volumes and excess methane adsorption isotherms. (15th June 2020) - Yu, Xinran; Li, Jing; Chen, Zhangxin; Wu, Keliu; Zhang, Linyang; Yang, Sheng
Highlights: Helium and methane adsorption inside coal nano-slits is investigated by GCMC simulation. Effects of helium adsorption on determination of void volumes are illustrated. Suitable conditions for an accurate determination of void volume are obtained. Excess isotherms of methane calculated by apparent and referred volumes are compared. Abstract: A void volume, which is measured by helium expansion tests and used in the calculation of methane adsorption amounts, is always overestimated due to helium adsorption. In this study, by comparing void volumes of carbon nanopores determined under different temperatures and pressures using GCMC (Grand Canonical Monte Carlo) simulation, suitable experimental conditions for helium expansion tests are obtained. Five volumes, including one apparent volume Vapp, three referred volumes Vref and one physical volume Vphy, are recognized. The apparent volume Vapp corresponds to the volume directly determined under traditional experimental conditions, while three referred volumes are determined at 500 K with different pressure ranges (low, moderate, high). The physical volume is calculated by multiplying a pore width and a surface area. Besides, a volume determined by using a helium probe is named an accessible volume Vacc and used as a criterion for a determined volume through mass balance. It is found that use of a void volume determined under traditional experimental conditions or a physical volume leads to negative adsorption amounts at high pressures. Considering an economic effect and measurement accuracy, determining a void volume by helium expansion tests within a moderate pressure range at 500 K is suggested. Excess isotherms of methane calculated by the suggested volume are more appropriate and of great physical meanings for further investigation of adsorption mechanisms.